Analisis Aspek Emotional dan Spiritual Capital Terhadap Peningkatan Produktivitas Kerja Pengrajin Desa Wisata Keris - Silmi Hidayati; Zainiyatul Afifah (Journal of Management and Bussines (JOMB), 2023)
This research aims to analyze aspects of the application of emotional and spiritual capital in increasing the work productivity of craftsmen. This research uses a qualitative descriptive approach method with observation, interviews and literature studies as data sources. The research method used is the Miles and Huberman method, TRUSTWORTHINESS is used to replace "validity and reliability". The results of the research show that the application of emotional and spiritual capital is carried out quite well, although there is still a need to increase awareness and intention to make keris as the main motivation in efforts to increase work productivity. Keywords: Tourism Village, Emotional Capital, Spiritual Capital, Work Productivity